Analysis of Impurities in Sulfur Hexafluoride Gas via Gas Chromatography Based on Enhanced Plasma Detector. Issue 1 (1st February 2023) - Luo, Zongchang; Zhang, Longfei; Tang, Bin; Liang, Qinqin; Pan, Jiqi; Hu, Mengzhu
Abstract: An analytical method for detecting impurities in high-purity sulfur hexafluoride (SF6 ) gas is established by using gas chromatography (GC) based on the enhanced plasma detector (EPD). The concentration of impurities (hydrogen, oxygen, nitrogen, methane, carbon monoxide, carbon dioxide, carbon tetrafluoride, hexafluoroethane, and octafluoropropane) can be quantitatively detected through one-time sampling and external standard method, and the minimum detection limit of each component is calculated to be about 0.1ppm, the RSD of the test results is less than 3%. This method can meet the requirements of detecting the purity of SF6 gas used in electrical equipment.